AN ALGORITHM FOR SOLVING INTUITIONISTIC FUZZY LINEAR BOTTLENECK ASSIGNMENT PROBLEMS - Gani, A. Nagoor; Kavikumar, J.; Mohamed, V.N. (Journal of Technology Management and Business, 2015)
The linear bottleneck assignment problem (LBAP), which is a variation of the classical assignment problem, seeks to minimize the longest completion time rather than the sum of the completion times when a number of jobs are to be assigned to the same number of workers. If the completion times are not certain, then it is said to be a fuzzy LBAP. Here we propose a new algorithm to solve fuzzy LBAP with completion times as intuitionistic fuzzy numbers.